Homogeneous Catalyzed Aryl–Aryl Cross-Couplings in Flow - Ashikari, Yosuke; Nagaki, Aiichiro (Synthesis, 2021)
Aryl–aryl cross-coupling reactions are important reactions for the production of various biaryl compounds. This short review covers the various aryl–aryl cross-coupling reactions carried out in flow, focusing on the metal species of the aryl nucleophiles used in the cross-coupling reactions.1 Introduction2 Suzuki–Miyaura Coupling (B)3 Migita–Kosugi–Stille Coupling (Sn)4 Negishi Coupling (Zn)5 Kumada–Tamao–Corriu Coupling (Mg)6 Murahashi Coupling (Li)7 Conclusion
Keywords: flow microreactors; cross-coupling; reaction integration; aryl metals; flow synthesis